2016
DOI: 10.11604/pamj.2016.23.135.8630
|View full text |Cite
|
Sign up to set email alerts
|

Trend in mortality from a recent measles outbreak in Cameroon: a retrospective analysis of 223 measles cases in the Benakuma Health District

Abstract: IntroductionMeasles is a highly contagious viral infection with high mortality in poorly vaccinated regions. We sought to establish the trend in mortality and the factors that favoured the recent measles outbreak that occurred in Benakuma, in the North west region of Cameroon from the 21/06/2015 to 26/09/2015.MethodsWe carried out a retrospective register analysis of 223 measles cases. Time trends were established using the Mann-Kendall test while survival was assessed using the Kaplan-Meier survival analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…The report of the French health authorities in April 2018 reported 1527 cases of measles since the beginning of the year. In Central Africa, Cameroon reported the endemic circulation of the B3 MeV genotype between 2010 and 2011 and during a recent measles outbreak in 2015 [22, 23]. In Gabon, this study is the first to describe the circulation of genotype B3.…”
Section: Discussionmentioning
confidence: 89%
“…The report of the French health authorities in April 2018 reported 1527 cases of measles since the beginning of the year. In Central Africa, Cameroon reported the endemic circulation of the B3 MeV genotype between 2010 and 2011 and during a recent measles outbreak in 2015 [22, 23]. In Gabon, this study is the first to describe the circulation of genotype B3.…”
Section: Discussionmentioning
confidence: 89%
“…This study showed that case fatality was significantly higher in children vaccinated with two doses of vaccine (5.24%) as compared to either ones vaccinated with one dose (2.29%) or unvaccinated ones (0.68%) but other studies showed that mortality was significantly associated with unvaccinated status. 14,17,19,24 The case fatality was significantly higher in males vaccinated with two doses of vaccine as compared to either ones vaccinated with one There were 14.18% children in this study who had measles before ≤ 9 months of age while other national studies 11,20,25,31,32 showed 13.5% -54.4% had measles before ≤ 9 months of age.…”
Section: Discussionmentioning
confidence: 53%
“…3 he case fatality rate was 2.87% in this study. The national studies 20,25 showed lower case fatality rate while other ones 14,15,16,17,19,24 gave higher values (3.41% -16%). The international studies 22,23,[26][27][28][29] also gave variable results from 0-8.5%.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations